Effects of Enteral Olive Oil Supplement on Weight Gain, Length of Hospital Stay, and the Development of Some Complications in Preterm Infants: A Randomized Controlled Trial - Selin Aytemiz; Murat Sarı; Sadık Yurttutan; Yasemin Çıkar; Sümeyra Topal; Sinem Yalnızoğlu Çaka (Galenos Yayinevi, 2024)
Aim: The objective of the present research was to compare the nutritional status, weight gain, length of hospital stay, and the development of some complications in very low birth-weight (VLBW) infants who received and those who did not receive olive oil supplementation enterally. Materials and Methods: This study was a single-blind, randomized controlled trial with 96 VLBW infants (intervention: 48, control: 48) in a neonatal intensive care unit. In this study, those infants who met the inclusion criteria for the study were divided into two groups by using a random number table. The same feeding protocol (breast milk and/or formula milk) was applied to the infants in both groups. From the seventh day of life (after starting to take 25-30 mL/kg/day orally), 0.5 cc/30 mL of olive oil was added to the milk at each feeding of those infants in the intervention group. Results: In comparison with the control group, the infants in the intervention group had a higher daily weight gain rate in the first month and a higher weight on the tenth day, a shorter transition time to full enteral feeding, a higher amount of calories on the day of transition to full enteral feeding, and a shorter length of hospital stay (p<0.05). Furthermore, the need for rectal enema and the prevalence of sepsis, gastrointestinal system intolerance, and bronchopulmonary dysplasia were significantly lower in the intervention group in comparison with the control group (p<0.05). Conclusion: These findings suggest that olive oil supplementation administered enterally to preterm infants can be recommended since it positively affects the development of infants. Trial registration: This study was registered in ClinicalTrials.gov with the following ID: NCT05815849. This study was retrospectively registered on the 14th of April, 2023.